The Contribution Of Forest Honeybee As Non-Timber Forest Products To Local Communities Along The Kahayan River Basin Central Kalimantan - Arief Rahman Hakim; Asro Laelani Indrayanti; Teguh Pribadi; Elyta Vivi Yanti; Yosefin Ari Silvianingsih; Syaukani Syaukani (EnviroScienteae, 2020)
Field research was done to evaluate the financial benefits of forest honeybee business conducted by the local community at Kameloh Baru Village, Taruna Village, and Tumbang Nusa Village in Central Kalimantan. These villages studied are known as a natural honeybee-producing center in Central Kalimantan. The local tribe gathers forest honeybee from Apis dorsata that have done for generations. The results revealed that the income of forest honeybee gathering people in 2015 amounted to IDR six to ten million once harvest. The owner of a tree of honeybee nest has five times higher income than harvesters. However, after a forest fire in 2015, revenues in 2016 and 2017 dropped dramatically to 25% of the previous year. The depletion of natural food resources is a leading factor in honeybee production decrease. On the other hand, the farmers do not have the initiative to cultivate the host trees and reserve natural food resources. Forest honeybee cannot be harvested regularly, although the market demand for forest honeybee is still tremendous. On the other hand, a proper technique of honeybee harvesting did not conduct so that the resulting honeybee quality decreases. Neverthenless, the local tribe can develop sustainable forest honeybee gathering based on their ecological knowledge as incentives for forest conservation.